2009
DOI: 10.1016/j.freeradbiomed.2008.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Supression of hemin-mediated oxidation of low-density lipoprotein and subsequent endothelial reactions by hydrogen sulfide (H2S)

Abstract: Heme-mediated oxidative modification of low-density lipoprotein (LDL) plays a crucial role in early atherogenesis. It has been shown that hydrogen sulfide (H(2)S) produced by vascular smooth muscle cells is present in plasma at a concentration of about 50 micromol/L. H(2)S is a strong reductant which can react with reactive oxygen species like superoxide anion and hydrogen peroxide. The current study investigated the effect of H(2)S on hemin-mediated oxidation of LDL and oxidized LDL (oxLDL)-induced endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 51 publications
5
36
0
Order By: Relevance
“…The impact of hemin-induced eryptosis on microcirculation may be compounded by effects of hemin on endothelial cells. Hemin induces oxidative stress in endothelial cells [2,18,33,34]. On the one hand, hemin-induced oxidative stress may stimulate apoptosis of nucleated cells [7,47]; on the other hand, it upregulates heme oxidase [2,15,18,30], which in turn confers resistance to apoptosis [2,30,66].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of hemin-induced eryptosis on microcirculation may be compounded by effects of hemin on endothelial cells. Hemin induces oxidative stress in endothelial cells [2,18,33,34]. On the one hand, hemin-induced oxidative stress may stimulate apoptosis of nucleated cells [7,47]; on the other hand, it upregulates heme oxidase [2,15,18,30], which in turn confers resistance to apoptosis [2,30,66].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative modification of low-density lipoprotein plays a crucial role in early atherogenesis. Jeney and co-workers (26) found that H 2 S inhibited hemin-induced oxidative modification of LDL through a mechanism involving a reduction of lipid hydroperoxide content. As such, the direct or indirect modulation of intracellular ROS level by H 2 S may have important implications in the development of atherosclerosis.…”
Section: H 2 S In Atherosclerosismentioning
confidence: 99%
“…NaSH treatment reverses LPS (lipopolysaccharide)-induced iNOS expression and NO release Muzaffar et al 2008) and prevents homocysteine-induced toxicity and subsequent ROS formation in VSMCs (Yan et al 2006). Likewise, exogenous H 2 S attenuates oxidised low-density lipoprotein (oxLDL)-induced cytotoxicity in cultured HUVECs and was shown to protect against atherosclerosis (Laggner et al 2007a, b;Jeney et al 2009). The anti-atherosclerotic effect of H 2 S is further supported by the reported inhibition of platelet aggregation (Zagli et al 2007), inhibition of VSMCs proliferation (Du et al 2004) and reduction of neointima formation of balloon-injured carotid arteries (Meng et al 2007).…”
Section: H 2 S: a Novel Therapeutic Agent In Age-associated Pathologies?mentioning
confidence: 99%